Optimal Utilization of Oil Revenues in Economic Development: An Application to Dynamic Multi-Sectoral Planning for Nigeria - Jideonwo, John Azukaego (My University, 1979)
Since the oil crisis of 1973-74, the problem faced by the typical oil-producing country has been that of developing a production structure with which the excess supplies of financial capital available to it could be transformed into human and physical capital over time. Because the inflows of oil funds were unanticipated, the initial attempt at the utilization of such funds resulted in the haphazard piling up of imports at rates which did not correspond to the absorptive capacity of a non-industrial oil-producing economy, thereby limiting the contribution of these oil revenues to development. This study suggests a framework within which the inflow of oil-funds can be reasonably anticipated and .the rate of oil production in each OPEC member-country geared towards its absorptive capacity. The model is applied within the context of dynamic multi-sectoral planning for Nigeria over the period 1974 to 2001. This study has a distinct two-tier approach to the optimal determination of oil-production and oil-revenue utilization for OPEC as a whole and for Nigeria in particular. First, a dynamic programming model of the world oil market with OPEC as a monopolistic organization trying to maximize the discounted stream of net revenues accruing to its members is developed and solved. Then, the optimal rate of oil extraction determined is allocated to individual OPEC members on the-basis of historical market shares. In the second part of the study, the results of the oil sub-model were integrated with a dynamic multi-sectoral planning model with the anticipated revenues as maximum levels of uncompensated transfers of funds from the oil sector for financing the plan. In this way, Nigeria's capacity to absorb oil revenues can be determined in an optimal way. This procedure was applied to long term planning for Nigeria over nine planning periods from 1974 to 2001 by use of large-scale linear programming techniques. Simulation experiments were also conducted with the planning model in order to determine the effects of changes in the model's basic parameters on the economy's absorptive capacity and the major macroeconomic variables. Our results indicate that Nigeria's capacity to absorb oil revenues far exceeds the revenue-inflows that could derive from current allocations to it by OPEC. Thus, Nigeria can be expected to agitate for increases in the market share allocated to it by OPEC or to seek further increases in oil price while keeping within OPEC production norms. This would be particularly profitable for Nigeria up to 1986 after which it would probably reach the limit ·of its absorption capacity. Our computational experience with the planning model also indicates that Nigeria's future prospects will depend on several goals embodied in the model as contraints, the most important of which are -the rate of growth of imports that is permitted by explicit government policy, the savings rate that is set as a target, and the manner in which the export earnings from the oil sector are made available to the domestic economy.
Keywords: oil crisis, excess supplies, finanial capital, human, physical, funds, economy, oil production, multi-sectoral